Association of Life’s Crucial 9 with all-cause and cardiovascular mortality in stroke survivors and predictive value for mortality compared with Life’s Essential 8: evidence from NHANES 2005–2018 - Wu, Xupeng; Li, Xiaofeng; Liu, Hong (Frontiers in Neurology, 2025)
BackgroundThere is evidence of a positive correlation between depressive disorders and poor cardiovascular health (CVH). Recently, the inclusion of psychological health assessments into Life’s Essential 8 (LE8) has been put forward to enhance the foundation of CVH. We aimed to investigate the probable link between the innovative CVH assessment framework, Life’s Crucial 9 (LC9), and overall mortality as well as mortality associated with cardiovascular disease (CVD) among stroke survivors, while also assessing its prognostic relevance regarding mortality in comparison to LE8.MethodsThis study draws on a cohort of stroke survivors identified from the National Health and Nutrition Examination Survey (NHANES), spanning survey cycles from 2005 to 2018. The LE8 was assessed by the approach recommended by the American Heart Association. The LC9 framework incorporated an additional depression score, measured by Patient Health Questionnaire-9, into the LE8 assessment. To investigate the associations between LE8 and LC9 with all-cause and cardiovascular mortality in stroke survivors, we employed multivariable Cox proportional hazards regression analyses.ResultsAfter adjusting for covariates, each 10-point increase in LC9 was associated with a 24.5 and 30.1% reduction in all-cause and CVD mortality in stroke survivors, respectively. Participants in the highest quartile (Q4) of LC9 exhibited significantly lower mortality rates compared to those in the lowest quartile (Q1) (all-cause mortality: HR 0.412, p < 0.0001; CVD mortality: HR 0.327, p < 0.001). Similar associations were observed for LE8. Restricted cubic spline analysis indicated that both LC9 and LE8 demonstrated linearly associations with mortality post-stroke. Physical activity score, nicotine exposure score, and blood glucose score were significantly linked to all-cause and CVD mortality in stroke survivors. Adding depression score to LE8 significantly enhanced the prediction of all-cause mortality in stroke survivors (net reclassification improvement index = 9.6%, p = 0.033; ΔC index = 0.002, p = 0.0009; integrated discrimination improvement = 0.01, p = 0.007). The NRI of 9% (p = 0.086) for CVD mortality, while not statistically significant, suggests a trend toward improved classification.ConclusionLC9 exhibited both linear and inverse correlations with all-cause and cardiovascular mortality among stroke survivors. Adding a depression score to the LE8 framework may improve the predictive accuracy for all-cause mortality in stroke survivors.